Voice of the Customer: Creating Client Centered Cultures in Accounting Firms for Retaining Clients and Increasing Profitability - Leisa Gill; Vikkie McCarthy; David Grimmett (STIE Malangkucecwara, 2019)
Client satisfaction and retention books line the shelves of library business sections and are frequently the subjects at conferences and online blogs. The relationship between client satisfaction and profitability is often assumed, yet not prioritized or measured. Instead, industries and companies are continuously developing new clients by selling their goods and services. The ability to compete simply on product or service no longer exists, and with the evolution of technology, customers are continuously inundated with noise. However, one could argue the greatest voice to take cues from is that of the client – meeting their needs and solving their problems. Using a case comparison method, we found that a combination of voice of the client (VoC) and “Kaizen” leads to higher levels of client satisfaction and retention levels in accounting firms.